Spatiotemporal dynamics of evapotranspiration in the Yellow River Basin: implications of climate variability and land use change - Sheheryar Khan; Huiliang Wang; Muhammad Waseem Boota; Umer Nauman; Ali Muhammad; Zening Wu (Geomatics, Natural Hazards & Risk)
The Yellow River Basin (YRB) has experienced substantial fluctuations in climate and alterations in land use and land cover change (LUCC). Hence, our research aims to examine the impact of climate change and LUCC on surface evapotranspiration (ET) during the period 2000 to 2020. The data are obtained from MODIS products in comparison with water balance model. The study examined the correlation between ET and meteorological parameters, including precipitation (Pr), temperature (Temp), relative humidity (Rh), wind speed (U10) and net radiation (Rn), using the CHIRPS, ERA5 and FLDAS datasets. The Theil-Sen slope estimator and Mann-Kendall (M-K) test were utilized to assess the amplitude and statistical significance of trends in ET. The study thoroughly examined the annual and seasonal patterns. The yearly mean ET of 568.2 mm increased by approximately 11.43% and 7.30% during growing season. The recorded figure of 485.6 mm for the summer is significantly elevated, linked to higher Temp and U10. With hike of 21.06% in spring and urbanization from 242,749.5 km2 to 463,351.7 km2, although 1,595,073.5 km2 remained croplands, Rh and Pr have a strong negative association with ET (r = −0.747) and (r = −0.718), respectively. Meteorological factors have a diverse effect as Rn, Temp and U10 increase ET, while Pr and humidity decrease ET.